2020
DOI: 10.1177/0275074020909514
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Management in Public Organizations: Profiling the Public Entrepreneur as Strategist

Abstract: Our core argument is that the entrepreneurial school of thought in strategic management as conceptualized by Mintzberg and colleagues holds explanatory value for advancing knowledge about the behavior of public sector organizations, as it does for private firms, albeit with important qualifications when applied to public services: chiefly, the temporal limitation in post for the office-holder of a public organization. After describing our methods, we present qualitative data from a longitudinal case study of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 59 publications
0
12
0
6
Order By: Relevance
“…4 The most comprehensive literature review of dynamic capabilities in the public sector to date ( Piening, 2013 ) shows that our existing frameworks focus on exogenous sources of dynamism. Similarly, entrepreneurial approach to strategy and leadership in public-sector organizations tends to focus on the importance of individual leaders and teams in driving strategic initiatives ( Ongaro and Ferlie, 2020 ). Thus, the capacities associated with the public sector tend to be narrow and focus on stability (i.e.…”
Section: Dynamic Capabilities Of the Public Sector: Agility And mentioning
confidence: 99%
“…4 The most comprehensive literature review of dynamic capabilities in the public sector to date ( Piening, 2013 ) shows that our existing frameworks focus on exogenous sources of dynamism. Similarly, entrepreneurial approach to strategy and leadership in public-sector organizations tends to focus on the importance of individual leaders and teams in driving strategic initiatives ( Ongaro and Ferlie, 2020 ). Thus, the capacities associated with the public sector tend to be narrow and focus on stability (i.e.…”
Section: Dynamic Capabilities Of the Public Sector: Agility And mentioning
confidence: 99%
“…My study indicates that in some public sector organizations, innovation capability can have its "source" of dynamism in the dynamic managerial capabilities (Helfat & Martin, 2015) of public entrepreneurs. This is important because the prior studies have indicated the critical role of public managers in creating or improving public value (Ongaro & Ferlie, 2020;Trivellato et al, 2021). For example, Piening (2013) observed that dynamic capabilities in public sector organizations are dependent on "how extensively and appropriately public managers use established dynamic capabilities" (p. 236) However, to the best of my knowledge, my study is one of the first in the field of dynamic capabilities to acknowledge that public sector employees and lower-level managers themselves can possess and use their dynamic capabilities to continuously develop and implement innovations.…”
Section: Discussionmentioning
confidence: 99%
“…Our current understanding of dynamic capabilities in public sector organizations is that they rely on innovation-stimulating routines, processes, tools, and structures-dynamic organizational capabilities-in directing strategic change (Piening, 2011). However, the importance of exploring how public managers affect strategic change in public sector organizations has also been noted in the more recent research (Ongaro & Ferlie, 2020).…”
Section: The Current State Of Knowledge On the Dynamic Capabilities Perspectivementioning
confidence: 99%
“…One of the economic policies taken by the government is to provide tax incentives. This is done to boost investment by providing measurable convenience to the private sector [12]. To attract new investors or retain existing investors.…”
Section: Tax Intensive During the Pandemicmentioning
confidence: 99%